THE EFFECTIVE PROCESSING MODEL OF THE BUSINESS PLAN FOR THE AGRICULTURAL PRODUCTS - Vignjević Đorđević, Nada; Jevtić, Slavena; Jevtić, Nemanja (Economics of Agriculture, 2013)
The global financial crisis is caused by the structural disturbance, sudden lack of capital and the huge mass of liquid funds for regular maintenance of economic trends in the world. Highly developed countries are threatened with the risk of long-term recession. In the less developed countries, like ours, the global crisis had a much greater risk than the general financial collapse, due to limited resources to quickly overcome the financial insolvency. For Serbia, the way out of financial crisis lies in a faster start-up of available unused national resource, where a relatively small investment with a new fresh capital can create new job positions in very short time, GDP growth and the fastest routing of new products and export services. New Economic Development Strategy of Serbia depends on the skill and speed of running the huge resources available in the agricultural sector and industries that rely on the agricultural sector. The existence of more than 400,000 registered farms and with several thousand small and medium-sized companies for the processing of primary agricultural products and logistical support represent a real opportunity for a faster exit from the crisis. However, available resources in the agricultural sector are still very limited with range of products and services with a higher degree of processing, which could be offered to our traditional foreign buyers. Even though there are conditions for development of new export-oriented business ventures in Serbia, there is a lack of business ideas, knowledge and skills necessary to start such a business. In order to start new business ventures hundreds of good business plans must be provided in a very short period. A business plan is an important document for providing the necessary financial resources from public funds or from commercial banks. In crisis conditions, it is difficult to choose an appropriate subject of a new business plan. Thus, the authors paid special attention to defining the optimal choice of subjects and a business plan in a crisis atmosphere. The expected effects of reducing unemployment and creating new jobs were not achieved with the activities of government institutions in underdeveloped areas in the agricultural sector with the financing from foreign grants. This is a limiting factor for the faster way out of the crisis and the promotion of rapid economic growth. It emphasizes the importance of implementation of previous positive solutions to check market mobility of new programs, selection of the best technology and equipment, with the lowest cost per unit, in order to achieve competitiveness in the market in a crisis situation. A good business plan is based on a credible budgeting for the necessary financial resources, without which there will be no successful business. Proper analysis of the investment and business risk should provide security to entrepreneurs and owners of capital for investment given in the business plan. This research is primarily intended for current needs and implement in practice, as a contribution to more rapid initiation of new economic activities in the agricultural sector for the countrys rapid exit from the crisis that occurred.